PENGEMBANGAN DESAIN MOTIF DAN SISTEM PRODUKSI KERAJINAN KAIN (IJA) ACEH DI KECAMATAN SYIAH KUALA, KOTA BANDA ACEH - -, Wardiah (Mentari, 2009)
The empowerment of small handicraft industry is one of the government priority program aiming at developing the economy, thus included the pattern design industry of Acehnese cloth in Kota Banda Aceh. The fact shows that there are many obstacle in developing Acehnese art designed cloth industry; both are from the pattern design and production system applied. The long term goal is to improve the pattern design and the working efficiency of craft people in developing the business to be small industry business. Mean while, this project is aiming at finding out the ability of pattern design for various Acehnese cloth types during the production as well as identification of supporting factors and obstacles in improving the product.Â  The primary data were obtained from female crafters for the purpose of making sample. The instruments used in gathering the data were interview and observation, where the data was analyzed by using qualitative approach. The result showed that the richness of pattern and ornamental design required further development in differnt area such variety of pattern design of Acehnese cloth, the building pattern, the kings head letters, traditional cloths an curves from the kings gravestone. As the improvement of art pattern design of Acehnese cloth, it is required that the products of Acehnese cloth not only intended for male or female wearing but also in form or sarong and curtain. Conclusion, the products of Acehnese cloth which made for pre clothing have Acehnese pattern design by high quality stamp batik work and draw batik.Â Key words: pattern design, Acehnese cloth, small industry